THE USE OF BAHASA INDONESIA (L1) IN THE INTENSIVE ENGLISH (L2) CLASSROOM - Tria Agustin, Dery; -, Warsono; Mujiyanto, Januarius (English Education Journal, 2015)
This study was designed to explore, describe, and explain the use of studentsâ native language (Bahasa Indonesia) in the intensive English classroomorganized by the Center for Language Development (PBB) of IAIN SyekhNurjati Cirebonas well as the lecturersâ and studentsâ attitudes towards it. It also sought to establish the role that Bahasa Indonesia actually played in the class. This study employed a mix-methods design.Â  For confirmations and clarificationsit observed 7 classes, surveyed 7 lecturers and 167 students, and interviewed 5 lecturers.Findings revealed that some amount of Bahasa Indonesia was used by both the lecturers and the students. Use of the mother tongue was mainly influenced by studentsâ level of English proficiency and the skill of language being taught. Both the lecturers and the studentsfound the L1 useful for teaching and learning culture-related issues and difficult concepts like grammar.Â  However, they also realized that use of the L1, at a certain extent, could be harmful for learning. It can be concluded that the L1 has the potential to be a tool for supporting teaching and learning and it is a lecturer who determines whether use of the L1 helps or hinders English language learning.